Manatee blues - Anderson, Laurie Halse (New York : Puffin Books, 2007)
While on a Florida vacation with Dr. Mac, Zoe, and Maggie, Brenna tries to rescue a baby manatee only to wind up in hot water with Dr. Mac and the local manatee rescue center.
First published in the United States by Pleasant Co. Publications, 2000.
5.1
5-8
5-8
Keywords: Endangered species -- Juvenile fiction; Manatees -- Juvenile fiction; Wildlife rescue -- Juvenile fiction; Endangered species -- Fiction; Manatees -- Fiction; Wildlife rescue -- Fiction; Endangered species -- Fiction; Manatees -- Fiction; Wildlife conservation -- Fiction; Florida -- Juvenile fiction; Florida -- Fiction; Florida -- Fiction